Pemberdayaan Masyarakat Pesisir melalui Optimalisasi Google My Business untuk Perluasan Pasar Produk Lokal Kecamatan Kempas Kabupaten Indragiri Hilir Riau - Bayu Fajar Susanto; Khairul Ihwan; Muannif Ridwan; Muchlis; Ahmad Rifai; Widyawati; Syafrinadina; Raju Maulana (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2026)
The community service program was carried out in Kecamatan Kempas, Kabupaten Indragiri Hilir, Riau, aiming to empower coastal communities through optimization of Google My Business (GMB) to expand the market for local products. The coastal communities in Kecamatan Kempas have abundant natural resource potential, yet they face challenges in marketing their products due to limited digital literacy and access to online marketing platforms. This program employed a Participatory Action Research (PAR) approach consisting of needs analysis, training, mentoring, and evaluation stages. The training involved 40 participants consisting of local entrepreneurs, fishermen, and village officials. The results showed a significant improvement in participants' understanding and skills in creating and optimizing GMB business profiles, managing product photos, responding to customer reviews, and utilizing GMB insights for business decision-making. After the program, 85% of participants were able to independently manage their GMB accounts and experienced an average increase of 35% in online customer inquiries. This program demonstrates that Google My Business optimization can be an effective strategy for expanding the market for local products in coastal areas and improving the economic welfare of coastal communities in Kecamatan Kempas, Kabupaten Indragiri Hilir, Riau.